Pregnancy in wornen aged 40 years and older: epidemiological characteristics - Ventura, Walter (2015)
OBJETIVES: To describe the epidemiological characteristics and obstetric and perinatal outcomes in pregnant women after 40 years. DESIGN: Descriptive Study retrospectivo.MATERIAL AND METHODS: The medical records of all births occurred in women 40 years or older treated at the IME of January 1, 2004 to November 30, 2004. Revised RESULTS: 18568 births were attended, of which 516 were women aged 40 or more, with an incidence of 2.78%. Two groups, the group of gilts (n = 46) and the group of multiparous (n = 470) was distinguished. 58.2% were between 40 and 42 years at birth. Both groups had similar characteristics in terms of average age, marital status, BMI and number of prenatal visits. The cesarean rate in the entire population was high (56.8%) and highest in nulliparous group (71.7%; p <0.01). The group of gilts showed higher instances of dysfunctional births, in which oxytocin (52.2%; p <0.05) was used. 15 (0.8%) intrauterine fetal deaths all occurred in multiparous women. There was a higher rate of preterm births in the general population, the nulliparous group had a rate of 21.7%, with no significant difference. Multiparous women had higher number of macrosomic infants (11.3%), the group of gilts (p <0.05). CONCLUSIONS: Older nulliparous 40 years have an increased risk of dysfunctional labor and higher rates of cesarean section and preterm and multiparous, increased risk of stillbirth and fetal macrosomia.